Perbedaan Tingkat Kecemasan Pada Pasien Pre dan Post Op di Ruang Seruni RSUD Pare - Moh Alimansur; Agung Setiawan (coba, 2013)
Action operate or surgery represent is the difficult experience for every patient. Ugly possibilities might possibly be happened to endanger for patient. Psikososial problem specially feeling fear and worry always experienced of each and everyone to surgery. Anxiety is one of natural emotion symptom by everybody in life. This research represent purposive to know the difference level of the anxiety at patient of pre and post operate. This research is Comparatif research. The population in pre and post operate with the amount sample much 62 responder (31 patient of pre and 31 of patient of post operate), using technique of Purposive Sampling, with the variable mount the anxiety at patient of pre operate and mount the anxiety at patient of post operate. Method of data collecting used by kuesioner HARS scale. Result from the research is the value r = 0,170, its meaning there is difference mount the anxiety at patient of pre and post operate. Expected from this research become the input for medical energy to more to paying attention to condition of psychology moment patient will experience the operation and remain to watch it until its condition return like from the beginning. Keyword : Difference, Anxiety, Pre, Post, Operate